Effect of Different Fungicides and Phytoextracts on Growth Inhibition of Alternaria burnsii - Pipliwal, S.K.; Jadeja, K.B.; Sharma, Anshul (Annals of Agricultural Research, 2017)
An experiment was conducted on cumin crop and the treatment set of fungicides and phytoextracts were tested for their inhibitory effect on spore germination of Alternaria burnsii causing cumin blight was performed in in vitro condition. In the laboratory screening systemic fungicides, hexaconazole, propiconazole, tebuconazole and non systemic fungicides, mancozeb executed 100 per cent growth inhibition of A. burnsii, the cumin blight pathogen. Among the phytoextracts tested against A. burnsii under in vitro conditions, Turmeric rhizome (70.55%), garlic clove (67.45 %) and ginger rhizome (62.79 %) at 10 per cent proved most effective phytoextracts for growth inhibition of A. burnsii.